Thin film shape memory alloys fundamentals and device applications - Fu, Yong Qing; Huang, Wei Min; Miyazaki, Shuichi (Cambridge University Press, 2009)
This book, the first dedicated to this exciting and rapidly growing field, enables readers to understand and prepare high-quality, high-performance TiNi shape memory alloys (SMAs). It covers the properties, preparation and characterization of TiNi SMAs, with particular focus on the latest technologies and applications in MEMS and biological devices. Basic techniques and theory are covered to introduce new-comers to the subject, whilst various sub-topics, such as film deposition, characterization, post treatment, and applying thin films to practical situations, appeal to more informed readers. Each chapter is written by expert authors, providing an overview of each topic and summarizing all the latest developments, making this an ideal reference for practitioners and researchers alike.